2016
DOI: 10.1177/1524838016683457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interviewer Support on Children’s Memory and Suggestibility: Systematic Review and Meta-Analyses of Experimental Research

Abstract: The accuracy of children's reports of abuse has been hotly debated in the press, academia, and the courtroom. Yet, children's accuracy depends, in part, on the context in which children are interviewed. Guidelines often recommend creating a supportive psychosocial context to promote open, honest responding; however, there is also concern that support promotes social desirability and acquiescence to suggestion, leading children to report more of what they perceive adults want to hear than the truth. The questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 58 publications
2
95
0
3
Order By: Relevance
“…In addition to their utility in fostering the credibility of children's testimony, we found that emotions fostered the retrieval of forensically valuable information. Previous analog studies have shown that informativeness (e.g., Davis & Bottoms, 2002;Quas, Bauer, & Boyce, 2004) and accuracy (for meta-analysis, see Saywitz et al, 2016) increase when interviewers adopt a supportive demeanor. There is also substantial evidence that emotions can enhance children's FACILITATING THE EXPRESSION OF EMOTIONS 16 memory retrieval (see Hamann & Stevens, 2014 for review) but this was the first study to examine displays of emotion in forensic contexts and to show that the expression of emotions accounts for the association between supportive interviewing and informativeness, suggesting an indirect pathway between support, emotion reinstatement, and retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their utility in fostering the credibility of children's testimony, we found that emotions fostered the retrieval of forensically valuable information. Previous analog studies have shown that informativeness (e.g., Davis & Bottoms, 2002;Quas, Bauer, & Boyce, 2004) and accuracy (for meta-analysis, see Saywitz et al, 2016) increase when interviewers adopt a supportive demeanor. There is also substantial evidence that emotions can enhance children's FACILITATING THE EXPRESSION OF EMOTIONS 16 memory retrieval (see Hamann & Stevens, 2014 for review) but this was the first study to examine displays of emotion in forensic contexts and to show that the expression of emotions accounts for the association between supportive interviewing and informativeness, suggesting an indirect pathway between support, emotion reinstatement, and retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of non-reluctant children were the first to show the beneficial effects of support on cognitive performance and interview outcomes when interviewers were warm and friendly, smiled, maintained eye contact, adopted open postures, and expressed interest in what the children said (e.g., Davis & Bottoms, 2002;Quas, Bauer, & Boyce, 2004). Further studies (for a meta-analysis, see Saywitz, Wells, Larson, & Hobbs, 2016) established that supportive interviews predicted more rather than less accurate information than did neutral or non-supportive interviews, even in response to suggestive questions. At least in these analog studies, however, supportive behavior was not associated with increases in the total amount of information provided, perhaps because the participants in such studies were highly motivated to be cooperative regardless of variations in the interviewers' behavior.…”
Section: Reluctant Children and Interviewer Behaviormentioning
confidence: 99%
“…In any case, in terms of general interviewing techniques, there is an abundance of empirical research showing that children are more accurate and less suggestible when interviewed by a supportive interviewer compared to when interviewed by an unsupportive or neutral interviewer (Davis and Bottoms 2002;Goodman et al 1991a;Hershkowitz et al 2006;Klemfuss et al 2013;Quas et al 2004;Quas and Lench 2007;Saywitz et al 2014;Saywitz et al 2016). Indeed, during police interviews, unsupportive or intimidating questioning is associated with increased suggestibility and impaired performance (Davies and Wescott 1999).…”
Section: Defendant Pro Se Cross-examination and Child Witness Accuracymentioning
confidence: 99%
“…It seems reasonable to expect these effects would be even stronger with a defendant pro se, who, as the accused, is likely to be viewed by the child as intimidating. Researchers recommend that if interviewers want to obtain the best possible information from children, the interviewers should be warm and friendly and have an objective nonjudgmental stance (Cronch et al 2006;Saywitz et al 2016).…”
Section: Defendant Pro Se Cross-examination and Child Witness Accuracymentioning
confidence: 99%
See 1 more Smart Citation